Epstein–Barr virus infection, B‐cell dysfunction and other risk factors converge in gut‐associated lymphoid tissue to drive the immunopathogenesis of multiple sclerosis: a hypothesis. Issue 11 (31st October 2022) - Leffler, Jonatan; Trend, Stephanie; Hart, Prue H; French, Martyn A
Abstract: Multiple sclerosis is associated with Epstein–Barr virus (EBV) infection, B‐cell dysfunction, gut dysbiosis, and environmental and genetic risk factors, including female sex. A disease model incorporating all these factors remains elusive. Here, we hypothesise that EBV‐infected memory B cells (MBCs) migrate to gut‐associated lymphoid tissue (GALT) through EBV‐induced expression of LPAM‐1, where they are subsequently activated by gut microbes and/or their products resulting in EBV reactivation and compartmentalised anti‐EBV immune responses. These responses involve marginal zone (MZ) B cells that activate CD4 + T‐cell responses, via HLA‐DRB1, which promote downstream B‐cell differentiation towards CD11c + /T‐bet + MBCs, as well as conventional MBCs. Intrinsic expression of low‐affinity B‐cell receptors (BCRs) by MZ B cells and CD11c + /T‐bet + MBCs promotes polyreactive BCR/antibody responses against EBV proteins (e.g. EBNA‐1) that cross‐react with central nervous system (CNS) autoantigens (e.g. GlialCAM). EBV protein/autoantigen‐specific CD11c + /T‐bet + MBCs migrate to the meningeal immune system and CNS, facilitated by their expression of CXCR3, and induce cytotoxic CD8 + T‐cell responses against CNS autoantigens amplified by BAFF, released from EBV‐infected MBCs. An increased abundance of circulating IgA + MBCs, observed in MS patients, might also reflect GALT‐derived immune responses, including disease‐enhancing IgA antibody responses against EBV and gut microbiota‐specific regulatory IgA + plasma cells. Female sex increases MZ B‐cell and CD11c + /T‐bet + MBC activity while environmental risk factors affect gut dysbiosis. Thus, EBV infection, B‐cell dysfunction and other risk factors converge in GALT to generate aberrant B‐cell responses that drive pathogenic T‐cell responses in the CNS. Abstract : A novel and comprehensive hypothesis for the pathogenesis of multiple sclerosis that incorporates immunological mechanisms and genetic and environmental risk factors is proposed. Activation of Epstein–Barr virus (EBV)‐infected memory B cells (MBCs) residing in gut‐associated lymphoid tissue results in lytic EBV infection that induces compartmentalised immune responses by marginal zone B cells and CD4 + T cells and production of CD11c + /T‐bet + memory B cells, influenced by genetic and environmental risk factors. EBV‐specific B‐cell receptors and antibodies produced by these B‐cell subpopulations are cross‐reactive with CNS autoantigens and the CD11c + /T‐bet + MBCs drive CD8 + T‐cell responses against CNS autoantigens.